Percepções e ações de professoras diante das manifestações de agressividade das crianças em uma instituição de Educação Infantil - Walquíria de Souza Euzébio (2018)
This work presents the results of a master's research that had as main objective to investigate the actions of teachers in front of demonstrations of aggressiveness of four and five years old children in a Municipal Unit of Early Childhood Education - UMEI of Belo Horizonte. The theoretical reference articulates to the areas of Early Childhood Education and Psychology, with the main contribution of studies by D. Winnicott that analyzes the aggressive behavior by a psychoanalytic perspective, in which aggressiveness is seen as constitutive, creative and necessary to the psychic development of the subject. A qualitative investigation was carried out, with document analysis, participant observation and semi-structured interviews with three teachers, pedagogical coordinators and the deputy director of the institution. These analyzes indicated that both in the documents and in the conception of the teachers the theme of aggressiveness was presented as a synonym of violence. The teachers demonstrated difficulties in differentiating the terms violence and aggression. We also identify a vision of the phenomenon to its negative side, which according to our theoretical framework hinders the educational action of children. Based on this analysis, we believe that there is still a need to move forward with regard to the understanding of aggression, not only in the educational field, but in all those in which human training is practiced and that for this, continuing education courses must be constantly offered to teachers and to contemplate the complex relationships that the teachers establish with the children.